Mitochondrial Iron Overload-Mediated Inhibition of Nrf2-HO-1/GPX4 Assisted ALI-Induced Nephrotoxicity - Deng, Hui-Fang; Yue, Lan-Xin; Wang, Ning-Ning; Zhou, Yong-Qiang; Zhou, Wei; Liu, Xian; Ni, Yu-Hao; Huang, Cong-Shu; Qiu, Li-Zhen; Liu, Hong; Tan, Hong-Ling; Tang, Xiang-Lin; et al. (Frontiers in Pharmacology, 2021)
Aristolactam І (ALІ) is an active component derived from some Traditional Chinese medicines (TCMs), and also the important metabolite of aristolochic acid. Long-term administration of medicine-containing ALІ was reported to be related to aristolochic acid nephropathy (AAN), which was attributed to ALІ-induced nephrotoxicity. However, the toxic mechanism of action involved is still unclear. Recently, pathogenic ferroptosis mediated lipid peroxidation was demonstrated to cause kidney injury. Therefore, this study explored the role of ferroptosis induced by mitochondrial iron overload in ALI-induced nephrotoxicity, aiming to identify the possible toxic mechanism of ALI-induced chronic nephropathy. Our results showed that ALІ inhibited HK-2 cell activity in a dose-dependent manner and significantly suppressed glutathione (GSH) levels, accompanying by significant increases in intracellular 4-hydroxynonenal (4-HNE) and intracellular iron ions. Moreover, the ALI-mediated cytotoxicity could be reversed by deferoxamine mesylate (DFO). Compared with other inhibitors, Ferrostatin-1 (Fer-1), a ferroptosis inhibitor, obviously alleviated ALІ-induced cytotoxicity. Furthermore, we have shown that ALI could remarkably increase the levels of superoxide anion and ferrous ions in mitochondria, and induce mitochondrial damage and condensed mitochondrial membrane density, the morphological characteristics of ferroptosis, all of which could be reversed by DFO. Interestingly, ALI dose-dependently inhibited these protein contents of nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and glutathione peroxidase 4 (GPX4), which could be partly rescued by Tin-protoporphyrin IX (SnPP) and mitoTEMPO co-treatment. In conclusion, our results demonstrated that mitochondrial iron overload-mediated antioxidant system inhibition would assist ALI-induced ferroptosis in renal tubular epithelial cells, and Nrf2-HO-1/GPX4 antioxidative system could be an important intervention target to prevent medicine containing ALI-induced nephropathy.